2022
DOI: 10.3390/ijms23105656
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide Alleviates Pulmonary Fibrosis Induced by Silica in Mice by Inhibiting ER Stress and the TLR4-NF-κB Pathway

Abstract: Silicosis is the most prevalent occupational disease in China. It is a form of pulmonary fibrosis caused by the inhalation of silicon particles. As there is no cure for the potentially lethal and progressive condition, the treatment of silicotic fibrosis is an important and difficult problem to address. Thalidomide, a drug with anti-inflammatory and immunoregulatory properties, has been reported to have lung-protective effects. The purpose of this study was to observe the therapeutic effect of thalidomide on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…TNF-α, as a downstream factor of the TLR4-NF-κB signaling pathway, is significantly down-regulated. 37 This is consistent with our experimental results, in our rosacea mice model, thalidomide could reduce the skin lesion area and inhibit inflammation by reducing the infiltration of inflammatory cells and the expression of TNF-α and IL-1β. Intestinal fibrosis is considered to be a common phenomenon in inflammatory bowel diseases.…”
Section: Discussionsupporting
confidence: 92%
“…TNF-α, as a downstream factor of the TLR4-NF-κB signaling pathway, is significantly down-regulated. 37 This is consistent with our experimental results, in our rosacea mice model, thalidomide could reduce the skin lesion area and inhibit inflammation by reducing the infiltration of inflammatory cells and the expression of TNF-α and IL-1β. Intestinal fibrosis is considered to be a common phenomenon in inflammatory bowel diseases.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that thalidomide inhibits angiogenesis via downregulation of VEGF and angiopoietin-2 in Crohn's Disease (Wang et al 2021 ) 37 Thalidomide protected against paraquat-induced lung injury through a miRNA-141/HDAC6/IκBα-NF-κB axis in rat lung fibrosis model and in the RLE-6TN cell model (Zheng et al 2021 ) 38 Thalidomide modulated ER-stress, through TLR4- NF-κB pathway in mouse model of silicosis. Silicosis is a common form of pulmonary fibrosis in China (Li et al 2022b ) 39 Thalidomide derivative CC-885 was found to be a Basonuclin 2 (BNC2) inhibitor. The transcript BCN2 is responsible for simulating fibrosis signalling in tissues (Bobowski-Gerard et al 2022 ) 40 Thalidomide effectively lowered skin lesions, inflammation and fibrosis related factors in rosacea mice model (Kang et al 2022 ) …”
Section: Introductionmentioning
confidence: 99%